High-level secretory production of leghemoglobin in Pichia pastoris through enhanced globin expression and heme biosynthesis. (November 2022) - Shao, Youran; Xue, Changlu; Liu, Wenqian; Zuo, Siqi; Wei, Peilian; Huang, Lei; Lian, Jiazhang; Xu, Zhinan
Graphical abstract: Highlights: Rate-limiting steps of heme biosynthesis were identified in P. pastoris . Heme pathway consolidation enhanced the secretion of functional leghemoglobin. Fermentation resulted in the highest secretory yield of hemoproteins ever reported. Abstract: Soy leghemoglobin is a key food additive that imparts meaty flavor and color to meat analogs. Here, a Pichia pastoris strain capable of high-yield secretory production of functional leghemoglobin was developed through gene dosage optimization and heme pathway consolidation. First, multi-copy integration of LegH expression cassette was achieved via both post-transformational vector amplification and CRISPR/Cas9 mediated genome editing methods. A combination of inducible expression and constitutive expression resulted in the highest production of leghemoglobin. Then, heme biosynthetic pathway was engineered to address challenges in heme depletion and leghemoglobin secretion. Finally, the disruption of ku70 was complemented in engineered P. pastoris strain to enable high-density fermentation in a 10-L bioreactor. These engineering strategies increased the secretion of leghemoglobin by more than 83-fold, whose maximal leghemoglobin titer and heme binding ratio reached as high as 3.5 g/L and 93 %, respectively. This represents the highest secretory production of heme-containing proteins ever reported.